Easy PRAM-Based High-Performance Parallel Programming with ICE - Ghanim, Fady; Vishkin, Uzi; Barua, Rajeev (IEEE transactions on parallel and distributed systems, 2018)
Parallel machines have become more widely used. Unfortunately parallel programming technologies have advanced at a much slower pace except for regular programs. For irregular programs, this advancement is inhibited by high synchronization costs, non-loop parallelism, non-array data structures, recursively expressed parallelism and parallelism that is too fine-grained to be exploitable. We present ICE, a new parallel programming language that is easy-to-program, since: (i) ICE is a synchronous, lock-step language so there is no need for programmer-specified synchronization; (ii) for a PRAM algorithm its ICE program amounts to directly transcribing it; and (iii) the PRAM algorithmic theory offers unique wealth of parallel algorithms and techniques. We propose ICE to be a part of an ecosystem consisting of the XMT architecture, the PRAM algorithmic model, and ICE itself, that together deliver on the twin goal of easy programming and efficient parallelization of irregular programs. The XMT architecture, developed at UMD, can exploit fine-grained parallelism in irregular programs. We have built the ICE compiler which translates the ICE language into the multithreaded XMTC language; the significance of this is that multi-threading is a feature shared by practically all current scalable parallel programming languages thus providing a method to compile ICE code. As one indication of ease of programming, we observed a reduction in code size in 11 out of 16 benchmarks as compared to hand-optimized XMTC. For these programs, the average reduction in number of lines of code was 35.5 percent. The remaining 5 benchmarks had almost the same code size for both ICE and hand-optimized XMTC. Our main result is perhaps surprising: The run-time was comparable to XMTC with a 0.53 percent average gain for ICE across all benchmarks.